Польські наукові історичні атласи в XIX–XX ст. - Конопська, Б. (Український історичний журнал, 2012)
Здійснено спробу класифікації польських наукових історичних атласів, а також
простежується еволюція картографічної думки. Стверджується, що в розвитку
концепції наукових історичних атласів можна виділити три етапи: до 1880 р.,
тобто до зародження польської наукової історичної картографії; завершення
Другої світової війни; кінець XX – початок XXI ст. Author attempts to classify the Polish scientific historical atlases and cartographic. Also,
in the article traces the evolution of cartography thought and asserts that in the concept
development of scientific historical atlases can pick out three stages: before 1880th, notably
before the initiation of the Polish scientific historical cartography, the end of Second World
War, the end of XX – early XXI.